Understanding X-ray and optical selection of galaxy clusters: a comparison of the XXL and CAMIRA cluster catalogues obtained in the common XXL-HSC SSP area. Issue 4 (26th March 2021) - Willis, J P; Oguri, M; Ramos-Ceja, M E; Gastaldello, F; Sereno, M; Adami, C; Alis, S; Altieri, B; Chiappetti, L; Corasaniti, P S; Eckert, D; Ettori, S; et al.
ABSTRACT: Large samples of galaxy clusters provide knowledge of both astrophysics in the most massive virialized environments and the properties of the cosmological model that defines our Universe. However, an important issue that affects the interpretation of galaxy cluster samples is the role played by the selection waveband and the potential for this to introduce a bias in the physical properties of clusters thus selected. We aim to investigate waveband-dependent selection effects in the identification of galaxy clusters by comparing the X-ray MultiMirror (XMM) Ultimate Extra-galactic Survey (XXL) and Subaru Hyper Suprime-Cam (HSC) CAMIRA cluster samples identified from a common 22.6 deg 2 sky area. We compare 150 XXL and 270 CAMIRA clusters in a common parameter space defined by X-ray aperture brightness and optical richness. We find that 71/150 XXL clusters are matched to the location of a CAMIRA cluster, the majority of which (67/71) display richness values N > 15 that exceed the CAMIRA catalogue richness threshold. We find that 67/270 CAMIRA clusters are matched to the location of an XXL cluster (defined within XXL as an extended X-ray source). Of the unmatched CAMIRA clusters, the majority display low X-ray fluxes consistent with the lack of an XXL counterpart. However, a significant fraction (64/107) CAMIRA clusters that display high X-ray fluxes are not associated with an extended source in the XXL catalogue. We demonstrate that this disparity arises from a variety of effects including the morphological criteria employed to identify X-ray clusters and the properties of the XMM PSF.